2023
DOI: 10.1002/cbdv.202200944
|View full text |Cite
|
Sign up to set email alerts
|

New Specific α‐Glucosidase Inhibitor Flavonoid from Thymelaea tartonraira Leaves: Structure Elucidation, Biological and Molecular Docking Studies

Abstract: The phytochemical investigation of Thymelaea tartonraira leaves led to the isolation and characterization of six compounds, including one new flavonoid glycoside identified as hypolaetin 8-O-β-D-galactopyranoside (4) along with five known compounds, daphnoretin (1), triumbelletin (2), genkwanin (3), tiliroside (5) and yuankanin (6). Their structures were established based on spectroscopic methods, such as UV, IR, NMR, and HR-ESI-MS. Triumbelletin (2) and tiliroside (5) were isolated for the first time from T. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The tested extracts demonstrated notable antioxidant potency through various mechanisms. Specifically, the methanol extract exhibited effectiveness in reducing Fe 3+ to Fe 2+ , converting Mo 6+ to Mo 5+ , and scavenging free radicals, which are known to pose significant health risks to humans [44]. The observed antioxidant activity of the methanolic extract from Cynoglossum tubiflorus leaves can be attributed to its abundant content of phenolic compounds and flavonoids, as suggested by previous studies [42].…”
Section: Total Antioxidant Activity (Tac)mentioning
confidence: 53%
See 1 more Smart Citation
“…The tested extracts demonstrated notable antioxidant potency through various mechanisms. Specifically, the methanol extract exhibited effectiveness in reducing Fe 3+ to Fe 2+ , converting Mo 6+ to Mo 5+ , and scavenging free radicals, which are known to pose significant health risks to humans [44]. The observed antioxidant activity of the methanolic extract from Cynoglossum tubiflorus leaves can be attributed to its abundant content of phenolic compounds and flavonoids, as suggested by previous studies [42].…”
Section: Total Antioxidant Activity (Tac)mentioning
confidence: 53%
“…The tested extracts demonstrated notable antioxidant potency through various mechanisms. Specifically, the methanol extract exhibited effectiveness in reducing Fe 3+ to Fe 2+ , converting Mo 6+ to Mo 5+ , and scavenging free radicals, which are known to pose significant health risks to humans [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ertas et al (2016) determined that the flavonoid content (19.66 ± 1.58 µg QEs/mg) and radical scavenging activity of the acetone extract (at a concentration of 100 µg/mL) was higher than other extracts prepared from the A. biennis. The antioxidant activity of tiliroside (the main compound of ABA-E) was investigated by different methods, including FRAP analysis (Ndhlala et al 2013, Li et al 2017, Soltani et al 2023. According to the study of Li et al (2017), the IC50 value of tiliroside in the FRAP analysis was found to be 246.8 ± 19.3 μg/mL (550.5 ± 42.9 μM).…”
Section: Discussionmentioning
confidence: 99%
“…Tricetin 4 -O-β-glucopyranoside (IC 50 = 1.17 mg/mL) and Tricetin (IC 50 = 0.43 mg/mL) both exhibited α-amylase inhibitory activities comparable to acarbose (IC 50 = 0.03mg/mL). In addition, a new α-glucosidase and α-amylase inhibitor flavonoid named hypolaetin 8-O-β-D-galactopyranoside (Figure 5e) was isolated from the leaves of Thymelaea tartonraira [140]. Yang et al [135] separated luteolin (Figure 5f) from Taraxacum mongolicum, which inhibits the α-amylase enzyme (IC50 = 42.33 μg/mL).…”
Section: Flavonoidsmentioning
confidence: 99%